2003
DOI: 10.1001/archpedi.157.12.1202
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Adoption of Home Smoking Restriction by Inner-city Black Smokers

Abstract: A smoker's motivation to quit and the presence in the home of a nonsmoking adult or of children predict adoption of HSR by inner-city black smokers. Therefore, health professionals should motivate the smoker toward HSR and the nonsmoking partner toward advocating home smoking bans, thereby eliminating environmental tobacco smoke in the home.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
21
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 33 publications
4
21
1
Order By: Relevance
“…These findings build upon previous research 23 and Hennessy and colleagues 35 , both which also reported that self-efficacy emerged as a significant predictor of HSBs even when accounting for other beliefs about SHSe.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…These findings build upon previous research 23 and Hennessy and colleagues 35 , both which also reported that self-efficacy emerged as a significant predictor of HSBs even when accounting for other beliefs about SHSe.…”
Section: Discussionsupporting
confidence: 87%
“…[16][17][18][19][20][21][22] Because these strategies require major behavioral changes, their success likely pivots on caregivers' confidence and motivation to reduce or eliminate sources of SHSe. 23 Yet, little is known about psychosocial and cognitive factors that influence HSB implementation or SHSe. General family psychosocial factors that affect children's well-being in other domains (e.g., academic, social) may also impact SHSe.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have consistently shown that smoke free workplace policies can substantially reduce daily cigarette consumption, increase cessation, and aid in the cessation process by providing a more supportive environment for those smokers making a quit attempt. 20 Although the preponderance of studies published to date have focused on the workplace, evidence is now beginning to accumulate on the correlation between home smoking restrictions and changes in smoker behaviour among both adults [25][26][27][28][29][30][31] and adolescents. [32][33][34] Analysing data from the earlier 1992-93 CPS, Farkas et al found a statistically significant correlation between home smoking restrictions and both quit attempts and successful quitting, defined as quit for six or more months, among more than 48 000 adult smokers; furthermore, household restrictions were more strongly correlated with both cessation outcomes compared with workplace restrictions.…”
Section: Discussionmentioning
confidence: 99%
“…26 Another study based on a stage of change model conducted among a small sample of inner city black smokers participating in a community cessation programme (n = 311), reported higher odds of adopting home smoking restrictions with increased progress in stages of change. 27 Gilpin et al investigated the association between home smoking restrictions and smoking behaviour among a random sample of Californian adult smokers in 1996. Intention to quit in next six months was significantly associated with restrictive home policies but only among those smokers whose family expressed a preference that the smoker did not smoke.…”
Section: Policy Implicationsmentioning
confidence: 99%